The Translation of Substitution and Ellipsis in Arabic Subtitling - Izwaini, Sattar; Al-Omar, Hafsa (Journal of Audiovisual Translation, 2019)
This paper investigates the trends in translating cohesive devices while subtitling English-speaking films into Arabic through examining a corpus of 20 films. It looks at how translators deal in particular with substitution and ellipsis and how their approaches serve the cohesiveness of the subtitles. The paper also looks at the translation shifts resulting from those approaches. The study is based on Halliday and Hasan's model of cohesion (1976). The analysis has found a considerable number of shifts occurring while dealing with the cohesion of the target texts. Repetition stands to be the most dominant cohesive tie that is used as a counterpart of substitution and ellipsis in the English originals, making explicitation the main strategy in translating such ties in Arabic subtitles. Substitution comes second while ellipsis and reference are found to be marginal. In their tendency to avoid ellipsis, translators opt for repetition or substitution as cohesive devices in Arabic subtitles.